Ocular fixations modulate audiovisual semantic congruency when standing in an upright position (2020)
Introduction: Multisensory audiovisual semantic congruency is the process by which visual information is perceived as integrated to auditory stimuli, because both coincide in terms of simultaneity and semantic correspondence. This study was aimed at establishing whether visual percepts, which semantically correspond to auditory stimuli, are associated with ocular fixations in modulating bottom-up areas while keeping a body posture alignment between the up-direction and the idiotropic axes, as well as in another orientation corresponding to a vectorial opposition between the up-direction and the head idiotropic axis. Method: Two groups (one for each position) were selected from a sample of 88 people. A bistable image was presented on a screen of a fixed 120 Hz eye-tracker device, providing background auditory stimuli so as to establish semantic congruencies and their relations to ocular fixations. Results: It was found that audiovisual semantic congruency is associated with fixations when idiotropic vectors are aligned with the up direction. Fixations manifested in bottom-up modulating areas are not associated with multisensory audiovisual semantic congruency when the head idiotropic vector is parallel with the gravity vector. Eye fixations decrease significantly if the head idiotropic axis is aligned with the gravity vector. Conclusion: It is concluded that body position can affect visual perceptual processes involved in the occurrence of semantic congruency. © 2021 Fundación Universitaria Konrad Lorenz. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).